Transcriptionally downregulated GABAergic genes associated with synaptic density network dysfunction in temporal lobe epilepsy. - Li, Rong; Xiao, Ling; Han, Honghao; Long, Hongyu; Liao, Wei; Yang, Zhenzhe; Zhu, Haoyue; Wang, Xuyang; Zou, Ting; Huang, Yongwen; Biswal, Bharat B.; Zhou, Ming; et al. (European Journal of Nuclear Medicine & Molecular Imaging, 2025)
Purpose: Temporal lobe epilepsy (TLE) is a brain network disorder closely associated with synaptic loss and has a genetic basis. However, the in vivo whole-brain synaptic changes at the network-level and the underlying gene expression patterns in patients with TLE remain unclear. Methods: In this study, we utilized a positron emission tomography with the synaptic vesicle glycoprotein 2 A radioligand [18F]SynVesT-1 cohort and two independent transcriptome datasets to investigate the topological properties of the synaptic density similarity network (SDSN) in TLE and its correlation with significantly dysregulated risk genes. Results: We observed an overall decrease in strength, reduced clustering coefficient, and increased path length of SDSN in TLE, suggesting a loss of connectivity that is accompanied by network reorganization. These changes were predominantly distributed in the temporo-limbic circuit and fronto-parietal networks. Moreover, connectivity changes in SDSN were found to be spatially correlated with the brain-wide expression of TLE risk genes, and the transcriptional correlate of SDSN changes showed a significant relationship with gene dysregulation. In particular, we identified a total of 183 downregulated genes that were functionally enriched for synaptic transmission pathways, forming a highly connected genetic interaction network. Within this set of genes, GABAergic genes such as RBFOX1 play a central role. Discussion: Our study provides the first evidence that the spatial expression patterns of downregulated risk genes underlie in vivo synaptic density network dysfunction in TLE. These imaging-transcriptomic findings have the potential to guide the development of molecular and genetic network-based therapeutic approaches for TLE.